Transcatheter versus Surgical Aortic Valve Replacement after Previous Cardiac Surgery: A Systematic Review and Meta-Analysis - Sharaf-Eldin Shehada; Yacine Elhmidi; Öznur Öztürk; Markus Kasel; Antonio H. Frangieh; Fanar Mourad; Jaroslav Benedik; Jaafar El Bahi; Mohamed El Gabry; Matthias Thielmann; Heinz Jakob; Daniel Wendt (Cardiology Research and Practice)
Aim. Aortic valve replacement (AVR) in patients with prior cardiac surgery might be challenging. Transcatheter aortic valve replacement (TAVR) offers a promising alternative in such patients. We therefore aimed at comparing the outcomes of patients with aortic valve diseases undergoing TAVR versus those undergoing surgical AVR (SAVR) after previous cardiac surgery. Methods and Results. MEDLINE, EMBASE, and the Cochrane Central Register were searched. Seven relevant studies were identified, published between 01/2011 and 12/2015, enrolling a total of 1148 patients with prior cardiac surgery (97.6% prior CABG): 49.2% underwent TAVR, whereas 50.8% underwent SAVR. Incidence of stroke (3.8 versus 7.9%, p=0.04) and major bleeding (8.3 versus 15.3%, p=0.04) was significantly lower in the TAVR group. Incidence of mild/severe paravalvular leakage (14.4/10.9 versus 0%, p<0.0001) and pacemaker implantation (11.3 versus 3.9%, p=0.01) was significantly higher in the TAVR group. There were no significant differences in the incidence of acute kidney injury (9.7 versus 8.7%, p=0.99), major adverse cardiovascular events (8.7 versus 12.3%, p=0.21), 30-day mortality (5.1 versus 5.5%, p=0.7), or 1-year mortality (11.6 versus 11.8%, p=0.97) between the TAVR and SAVR group. Conclusions. TAVR as a redo procedure offers a safe alternative for patients presenting with aortic valve diseases after previous cardiac surgery especially those with prior CABG.